Enhancing thermoelectric properties of NaCo2O4 ceramics through Na pre-treatment induced nano-decoration - Jakubczyk, E. M.; Mapp, A.; Chung, C. C.; Sansom, Christopher L.; Jones, J. L.; Dorey, Robert A. (Elsevier, 2019)
High quality NaCo2O4 thermoelectrics are challenging to process due to the volatile nature of Na, the slow densification kinetics, and degradation of NaCo2O4 above 900–950 °C leading to the formation of Na-poor second phases. Fine grained sol-gel derived powders have been used to enhance the densification kinetics while pre-treatment of the NaCo2O4 powder with NaOH, to provide a Na rich environment, has been shown to mitigate Na loss at elevated temperatures. While insufficient to compensate for Na loss at processing temperatures of 1000 °C and above, at lower temperatures it is able to enhance densification and facilitate the formation of complex crystal structures yielding low thermal conductivity (0.66 Wm−1K−1) coupled with high electrical conductivity (3.8 × 103 Sm−1) and a Seebeck coefficient of 34.9. The resultant room temperature power factor and ZT were 6.19 × 10−6 Wm−1K−2 and 0.0026, respectively.
Keywords: Ceramics; Thermoelectric materials; Oxide materials; Sol-gel processing; Scanning electron microscopy